A combining sliding mode control approach for electric motor anti-lock braking system of battery electric vehicle. (September 2020) - He, Lin; Ye, Wei; He, Zejia; Song, Ke; Shi, Qin
Abstract: In this paper, a combining sliding mode control (cSMC) approach of electric motor anti-lock braking system (emABS) is proposed to improve braking stability of battery electric vehicle (BEV). Two key variables, both wheel deceleration and slip ratio are utilized to design the emABS control law. Wheel deceleration directly characterizes the wheel speed, and slip ratio straightly characterizes some adhesion coefficient of ground. Based on sliding mode control (SMC) algorithm, two control laws of wheel deceleration and slip ratio are designed, the formula structures of which are very similar. At the same time, Lyapunov stability and robustness performance of the two control laws are proved, respectively. During the vehicle test, an interesting phenomenon was discovered that the SMC system of the wheel deceleration has fast transient response, and the slip ratio is more stability during stable control phase. The reason is that, the wheel deceleration can be measured accurately in the beginning, and the slip ratio can be computed accurately during stable control phase. Therefore, a SMC algorithm combined with wheel deceleration and slip ratio is designed for the control of emABS. With respect to low and high adhesion coefficient conditions, two simulation scenarios are utilized to validate the cSMC algorithm. In addition, the control strategy is verified on the test of BEV based on two road surfaces, the wet and the dry, respectively. These experimental results indicate that the proposed cSMC algorithm is a good candidate for the control of emABS. Highlights: A cSMC algorithm is designed for electric motor anti-lock braking system of BEV. Formula structures of SMC laws based on wheel deceleration and slip ratio are similar. The cSMC algorithm is validated by simulations and verified on the test of BEV. The cSMC algorithm for emABS improves slip ratio and wheel deceleration control quality.